2022
DOI: 10.3389/fphar.2021.818089
|View full text |Cite
|
Sign up to set email alerts
|

Fibrates for the Treatment of Primary Biliary Cholangitis Unresponsive to Ursodeoxycholic Acid: An Exploratory Study

Abstract: Aim: Up to 40% of patients with primary biliary cholangitis (PBC) will have a suboptimal biochemical response to ursodeoxycholic acid (UDCA), which can be improved by the addition of fibrates. This exploratory study aims to evaluate the long-term real-life biochemical response of different fibrates, including ciprofibrate, in subjects with UDCA-unresponsive PBC.Methods: The Brazilian Cholestasis Study Group multicenter database was reviewed to assess the response rates to UDCA plus fibrates in patients with UD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Recently, it has been reported that fibrates can be clinically useful in the treatment of hypertriglyceridemia and mixed hyperlipidemia and have anti-inflammatory, antifibrotic, and cholestasis-lowering effects. Fibrates can also ameliorate the biochemical characteristics of patients with PBC ( Cancado et al, 2021 ); Rosenson et al, 2007 , but the change in pruritus symptoms was not obvious. Although many observational studies have been published ( Cheung et al, 2016 ; Corpechot et al, 2018 ; Duan et al, 2018 ; Ghonem et al, 2020 ), the mechanism by which fibrates reduce the biochemical markers of cholestasis and whether the application of fibrates can improve the survival rate of patients with these diseases remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that fibrates can be clinically useful in the treatment of hypertriglyceridemia and mixed hyperlipidemia and have anti-inflammatory, antifibrotic, and cholestasis-lowering effects. Fibrates can also ameliorate the biochemical characteristics of patients with PBC ( Cancado et al, 2021 ); Rosenson et al, 2007 , but the change in pruritus symptoms was not obvious. Although many observational studies have been published ( Cheung et al, 2016 ; Corpechot et al, 2018 ; Duan et al, 2018 ; Ghonem et al, 2020 ), the mechanism by which fibrates reduce the biochemical markers of cholestasis and whether the application of fibrates can improve the survival rate of patients with these diseases remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PFIC2 patients may benefit from this type of pharmacological treatment [ 66 ]. The use of fibrates, such as the PPAR agonists bezafibrate, fenofibrate, and elafibranor ( Table 1 ), could also be beneficial for the treatment of PBC patients who do not respond to UDCA [ 67 ].…”
Section: Current Treatmentsmentioning
confidence: 99%
“…2 Cancado et al showed that 50% of UDCA nonresponders treated with add-on ciprofibrate or bezafibrate had a biochemical response at one year. 66 The combination of UDCA and bezafibrate decreased mortality and improved transplant-free survival compared with patients on UDCA monotherapy. 5,66 Pruritus was also significantly improved by bezafibrate in subjects with PBC.…”
Section: Fibratesmentioning
confidence: 99%